2021
DOI: 10.1371/journal.pone.0254093
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for post-thoracotomy pain: A systematic review and meta-analysis

Abstract: Background Thoracotomy is an invasive surgical procedure that produces intense postoperative pain. Electroacupuncture has been used to induce analgesia in various situations, including after surgery. The aim of the following systematic review and meta-analysis was to evaluate the effect of electroacupuncture on post-thoracotomy pain. Methods The studies for the systematic review were searched using the following 9 databases: PubMed, Cochrane Library, EMBASE, MEDLINE Complete, Google Scholar, China National K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…A total of 1286 articles related to eight conditions were searched (Table 1). After reviewing the abstract and full text of the article, 17 systematic reviews and meta-analyses of the six conditions that met the inclusion criteria were finally included [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and articles related to allergic rhinitis and chemotherapy-induced nausea and vomiting (CINV) did not meet the criteria for inclusion (Table 1).…”
Section: Results Of the Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1286 articles related to eight conditions were searched (Table 1). After reviewing the abstract and full text of the article, 17 systematic reviews and meta-analyses of the six conditions that met the inclusion criteria were finally included [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and articles related to allergic rhinitis and chemotherapy-induced nausea and vomiting (CINV) did not meet the criteria for inclusion (Table 1).…”
Section: Results Of the Searchmentioning
confidence: 99%
“…They found that auricular acupressure plus acupuncture, acupuncture, other acupuncture techniques, and auricular acupressure were significantly superior over usual care, and auricular acupressure plus acupuncture ranked the most effective when analyzed for pain intensity, but the findings were limited by the quality of the evidence. Park et al [29] assessed the quality of evidence in RCTs comparing pain scores between the EA and the sham groups, finding low cumulative evidence certainty across all studies. A low rating was given because there was inconsistency and a high risk of bias across all studies.…”
Section: Current Quality Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 , 10 ] Different acupuncture methods include manual acupuncture, electroacupuncture (EA), warm needling, auricular therapy, fire needling, etc., Currently, EA is one of the most common methods for treating pain in traditional Chinese medicine hospitals and has an excellent therapeutic effect on acute and chronic pain. [ 11 13 ] Recent studies have shown that EA can relieve pain by activating numerous bioactive chemicals through peripheral and central mechanisms and forestall the adverse impacts of often-debilitating pharmaceuticals. [ 14 ] Over recent years, some studies have confirmed that EA effectively relieves postherpetic neuralgia.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Electroacupuncture has shown good effects in many postoperative analgesic fields, such as pain after thoracotomy, abdominal pain after intestinal obstruction, pain after total hip replacement, pain after joint replacement, et cetera. [14][15][16][17][18] This meta-analysis will investigate the efficacy of electroacupuncture for postoperative pain in mixed hemorrhoids.…”
Section: Introductionmentioning
confidence: 99%